A semantic and pragmatic classification of the vocabulary of educational psychology research articles - Garofolo, Andrea (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This paper provides a classification of the vocabulary of the educational psychology research article based on semantic and pragmatic criteria. This study provides a description of a corpus of research articles in the field of educational psychology, focusing particularly on the coverage and frequency of the lexical items, based on the General Service List (GSL) and the Academic Word List (AWL). We analyzed and reclassified the most frequent words of the corpus according to semantic and pragmatic criteria, which revealed that a large number of words coming from the GSL and the AWL were not used with general or academic meaning in the field of educational psychology. This semantic and pragmatic classification allowed the compilation of a list of academic and technical words representative of the genre and discipline.